Cyber Security Training: ANN as an Evaluator and Informant (Journal of The Colloquium for Information Systems Security Education, 2014)
It is often agreed that security training and education is very important to the risk management strategy of an organization. However, it is not often possible to quantitatively measure the effectiveness of the delivered training. This paper presents a technique to help evaluate security training effectiveness through automated means. This technique employs artificial neural network as an informant to help analyze data. A case study on p2p downloading is presented.
Keywords: Training; Artificial Neural Network; Network Monitoring